Financial feasibility study of smallholder oil palm in Muaro Jambi District, Jambi. Issue 1 (October 2020) - Edison, E
Abstract: Research objectives were to explain smallholder oil palm production expenditure, to explain annual rate of their profit, to explain feasibility smallholder oil palm farming financially in Muaro Jambi District, Jambi. Study was conducted in in 2017. 86 samples were selected by sampling method purposively. Primary and secondary data was needed in this research. Research operated the calculation of TC = FC + VC to explain first objective. While I = TR − TC method was operated to explain second objective. In order to analyze last objective, some methods were operated. Research found that rate of its expenditure was in average level. Its cost included operation cost, labor cost and other cost. Rate of its profit each hectare was IDR 19.118.532.-while its rate per household was IDR 25.412.602.-Therefore, it can be said that smallholder oil palm farming was feasible.